The Impact Of Board Diversity On The Efficiency Of China’s Listed Commercial Banks - Jiang, Zhengyou (2019)
This study investigates the impact of board diversity on the efficiency of China’s listed commercial banks. First, we measure the efficiency of China’s listed commercial banks in post-crisis recovery era, by using the DEA method from Non-Parametric analysis approach. Then, we investigate the relationship between the board diversity and the efficiency measured from DEA tested results. The board diversity is represented by 4 different groups of directors, which are the independent director, foreign director, women director and political linked director